Use of Technology in Learning to Improve Early Childhood Concentration - Syamsiah, Siti; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Concentration is very important in early childhood so that children's learning outcomes can be more optimal. To improve children's concentration in learning, technology media can be used. The purpose of this study is to describe the use of technology in learning to improve the concentration of early childhood. Methodology: This study uses a descriptive qualitative method. The subjects of this study were teachers and students of group A at Tk Aisyiyah Kadipiro I. Data collection techniques were interviews, observations and documentation. Data analysis techniques were data reduction, data presentation, and data extraction conclusion. Results: The results of this study are that the use of technology can improve children's concentration in Aisyiyah Kadipiro I Kindergarten. Concentration can be seen from children being more focused, able to answer teacher questions, and a more conducive class. Applications/Originality/Value: To improve children's concentration in learning, technology media can be used.